BZP, a novel serum-responsive zinc finger protein that inhibits gene transcription. - Franklin, A J (1994)
We report the fortuitous isolation of cDNA clones encoding a novel zinc finger DNA-binding protein termed BZP. The protein encoded is 114 kDa and contains eight zinc finger motifs, seven of which are present in two clusters at opposite ends of the molecule. Both finger clusters bound to the 9-bp sequence AAAGGTGCA with apparent Kds of approximately 2.5 nM. Two of the finger motifs within the amino- and carboxy-terminal finger clusters share 63% amino acid identity. BZP inhibited transcription of the herpes simplex virus thymidine kinase promoter when copies of the 9-bp target motif were linked in cis, suggesting that it functions as a transcriptional repressor. BZP mRNA and immunoreactivity were detected in several established cell lines but were most abundant in hamster insulinoma (HIT) cells, the parental source of the cDNAs. In mouse tissues, BZP mRNA and immunoreactivity were identified in cells of the endocrine pancreas, anterior pituitary, and central nervous system. Interestingly, in HIT cells proliferating in culture, BZP immunoreactivity was predominately nuclear in location, whereas it was usually located in the cytoplasm in most neural and neuroendocrine tissues. Serum deprivation of HIT cells caused BZP immunoreactivity to become predominantly cytoplasmic in location and attenuated its inhibitory effect on transcription, thereby suggesting that the both the subcellular location and the function of this protein are modulated by factors in serum.